Sarcomatoid urothelial carcinoma arising in the female urethral diverticulum - Heae Surng Park (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
A sarcomatoid variant of urothelial carcinoma in the female urethral diverticulum has not been reported previously. A 66-year-old woman suffering from dysuria presented with a huge urethral mass invading the urinary bladder and vagina. Histopathological examination of the resected specimen revealed predominantly undifferentiated pleomorphic sarcoma with sclerosis. Only a small portion of conventional urothelial carcinoma was identified around the urethral diverticulum, which contained glandular epithelium and villous adenoma. The patient showed rapid systemic recurrence and resistance to immune checkpoint inhibitor therapy despite high expression of programmed cell death ligand-1. We report the first case of urethral diverticular carcinoma with sarcomatoid features.